Α-Glucosidase and α-amylase inhibitors from seed oil: A review of liposoluble substance to treat diabetes. Issue 16 (2nd November 2017) - Teng, Hui; Chen, Lei
ABSTRACT: One of the effective managements of diabetes mellitus, in particular, noninsulin-dependent diabetes mellitus, is to retard the absorption of glucose by inhibition of carbohydrate hydrolyzing enzymes, such as α-glucosidase and α-amylase, in the digestive organs. Currently, there is renewed interest in plant-based medicines and functional foods modulating physiological effects in the inhibition of α-glucosidase and α-amylase. Accordingly, inhibitors of α-glucosidase or α-amylase derived from various sources have also been isolated, and majority of phenolic compounds and their effects have been investigated in animals as well. As such, when the presence of α-glucosidase inhibitor in many foodstuffs was screened for, we found that vegetable seed oil also strongly inhibited α-glucosidase and α-amylase. Seed oil is an important source of liposoluble constituents with potential for inhibition of these enzymes, hence can also be used as therapeutic or functional food sources. Therefore, this review is aimed at highlighting the main liposoluble classes of α-glucosidase and α-amylase inhibitors, but it is not intended to be an exhaustive review on the subject.